2004
DOI: 10.1056/nejmoa032845
|View full text |Cite
|
Sign up to set email alerts
|

Folate Therapy and In-Stent Restenosis after Coronary Stenting

Abstract: Contrary to previous findings, the administration of folate, vitamin B6, and vitamin B12 after coronary stenting may increase the risk of in-stent restenosis and the need for target-vessel revascularization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
139
0
3

Year Published

2004
2004
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 300 publications
(145 citation statements)
references
References 34 publications
1
139
0
3
Order By: Relevance
“…But, the Swiss Heart Study demonstrated that homocysteine-lowering therapy did show significant risk reduction in major adverse cardiovascular events in patients treated with angioplasty, with or without stenting [30]. Finally, Lange et al evidenced that the multivitamin therapy, although reduced serum homocysteine levels, was associated with a paradoxical increase of restenosis and major adverse cardiac events at 6 months, particularly in patients with homocysteine levels in the normal range, whereas slight benefits were observed in patients with elevated homocysteine [31]. In the 14-year follow-up, the Nurses' Health Study Researchers suggested that intake of folic acid and vitamin B 6 may have positive impact on the primary prevention of heart disease among women and the maximum benefit would be achieved at folic acid intake of at least 400 lg/day [32].…”
Section: Therapy Of Hyperhomocysteinemiamentioning
confidence: 99%
“…But, the Swiss Heart Study demonstrated that homocysteine-lowering therapy did show significant risk reduction in major adverse cardiovascular events in patients treated with angioplasty, with or without stenting [30]. Finally, Lange et al evidenced that the multivitamin therapy, although reduced serum homocysteine levels, was associated with a paradoxical increase of restenosis and major adverse cardiac events at 6 months, particularly in patients with homocysteine levels in the normal range, whereas slight benefits were observed in patients with elevated homocysteine [31]. In the 14-year follow-up, the Nurses' Health Study Researchers suggested that intake of folic acid and vitamin B 6 may have positive impact on the primary prevention of heart disease among women and the maximum benefit would be achieved at folic acid intake of at least 400 lg/day [32].…”
Section: Therapy Of Hyperhomocysteinemiamentioning
confidence: 99%
“…Although there was no difference in the frequency of coronary stent placement between the two groups, others have reported that stent placement inhibits the beneficial effects of folic acid. In a subsequent study published by Lange et al [56], 636 patients were randomized to folic acid therapy or placebo after coronary stent placement. At 6 months, luminal diameter was smaller and in-stent restenosis rates higher in the treatment group.…”
Section: Coronary Angioplastymentioning
confidence: 99%
“…Of note, when tHcy levels were greater than 15 μmol/L, this effect was diminished. Explaining these contradictory data is difficult, but it is possible that a folic acid-induced antithrombotic state and improved endothelial function may benefit balloon angioplasty patients, whereas folic acid-induced cell proliferation may harm those receiving coronary stents [56,57].…”
Section: Coronary Angioplastymentioning
confidence: 99%
“…These results have led some interventionalists to adopt this vitamin strategy after coronary interventions, although if analyzed the data deeper, theses vitamin treatment seemed to be more effective after balloon angioplasty than after coronary stenting, being the latter now the method of choice for the vast majority of patients undergoing coronary intervention. This is why Lange et al [125] made a similar study using these vitamin treatment but only after stenting and found that folate therapy had adverse effects on the risk of restenosis in all subgroups except for women, patients with diabetes, and patients with markedly elevated homocysteine levels (15 µmol/L) at baseline, results that make the controversy about folate therapy grow.…”
Section: Hyperhomocysteinemia Treatmentmentioning
confidence: 99%